Colour and spectral reflectance of stools from normal neonatal babies. Issue 6 (7th October 2014) - Griffin, Lewis D.; Sutcliffe, Alastair G.; Bradbury, Kimberley; Kumble, Smitha; Mylonas, Dimitris; Baker, Alastair
Abstract Data is presented on the colour and spectral reflectances of stool samples from healthy young infants (mean age 6 days). The range of spectral reflectances is well described by a pigment mixture model with three components—a pale component corresponding to partially digested milk fats, a yellow component corresponding to bilirubin breakdown products, and a dark component corresponding to meconium and bilirubin. Most stools were tan, beige or olive but white, grey and light grey were also observed. © 2014 Wiley Periodicals, Inc. Col Res Appl, 40, 585–591, 2015